2010
DOI: 10.1093/glycob/cwq153
|View full text |Cite
|
Sign up to set email alerts
|

The human Cas1 protein: A sialic acid-specific O-acetyltransferase?

Abstract: Sialic acids are important sugars at the reducing end of glycoproteins and glycolipids. They are among many other functions involved in cell-cell interactions, host-pathogen recognition and the regulation of serum half-life of glycoproteins. An important modification of sialic acids is O-acetylation, which can alter or mask the biological properties of the parent sialic acid molecule. The nature of mammalian sialate-O-acetyltransferases (EC 2.3.1.45) involved in their biosynthesis is still unknown. We have ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 98 publications
1
47
0
Order By: Relevance
“…Under these conditions, the signal of H-10 (in the 2-position of the PBA group) was a singlet (see Figure 4c), as was the case for the signal of H-10 in the spectrum of monomeric SQ-BA2 in DMSO-d 6 . This fact suggests that the Fru−SQ-BA2 complex exists as a one-to-one, emissive, monomeric species in aqueous solution.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Under these conditions, the signal of H-10 (in the 2-position of the PBA group) was a singlet (see Figure 4c), as was the case for the signal of H-10 in the spectrum of monomeric SQ-BA2 in DMSO-d 6 . This fact suggests that the Fru−SQ-BA2 complex exists as a one-to-one, emissive, monomeric species in aqueous solution.…”
mentioning
confidence: 56%
“…The NMR spectra were obtained using a JEOL ECX-400 spectrometer operated at 400 MHz and a Bruker AVANCE500T spectrometer operated at 500 MHz for 1 H. Chemical shifts are reported in parts per million downfield from tetramethylsilane as the internal standard in DMSO-d 6 .…”
mentioning
confidence: 99%
“…The bioinformatics study of Anantharaman and Aravind (2010) indicated that the C-terminal domain of Cas1p and the plant RWA proteins belong to a larger class of acyltransferases with 10 transmembrane helices, whereas the N-terminal domain is an esterase domain. Another recent study showed that overexpression of the human Cas1 homolog in mammalian cells led to increased O-acetylation of sialic acid (Arming et al, 2010), suggesting that metazoan Cas1 homologs are sialic acid O-acetyltransferases. Sialyltransferase and overexpressed human Cas1 were shown to be colocalized in Golgi vesicles (Arming et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study showed that overexpression of the human Cas1 homolog in mammalian cells led to increased O-acetylation of sialic acid (Arming et al, 2010), suggesting that metazoan Cas1 homologs are sialic acid O-acetyltransferases. Sialyltransferase and overexpressed human Cas1 were shown to be colocalized in Golgi vesicles (Arming et al, 2010). Interestingly, it is known that mammalian O-acetylation of sialic acid takes place inside the Golgi vesicles by an integral membrane protein that utilizes acetyl-CoA from the cytoplasm to form an acetylated intermediate and releases CoA back into the cytoplasm (Higa et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, different RWA proteins may preferentially form complexes with a subset of TBL proteins. However, even in animals, it is not clear how the Cas1 protein mediates acetylation of sialic acid, and while Cas1 is definitely required, the acetylation could involve additional proteins (Arming et al, 2011).…”
Section: Discussionmentioning
confidence: 99%